HIMAFIS Mengabdi : Penerapan Pembelajaran Berbasis Proyek di Yayasan Al-Isro’ Desa Badrain, Lombok Barat - Thufail Mujaddid Al-Qoyyim; Baiq Andriani Saputri; Fahmi Firdaus; Johana Aulina Rahmatin; Nisrina Marliani; I Wayan Gunada (Jurnal Pengabdian Magister Pendidikan IPA, 2022)
The Covid-19 pandemic has had a negative impact on the learning process. The use of technology in online learning does not always have a good impact. Online learning provides more workload and homework. This also reduces students' motivation and willingness to learn. One of the areas where children experience decreased motivation to learn is Badrain Village. A learning model that can increase students' learning motivation is project-based (PjBL). This model provides projects to students. PjBL provides opportunities for students to interact and participate further in learning that is packaged in the form of group learning, to increase learning motivation after the pandemic. Therefore, HIMAFIS FKIP Mataram University carries out community service by implementing project-based learning to increase the learning motivation of children in Badrain Village. Service activities consist of three phases, namely the orientation phase, the learning phase, and the closing phase. This community service activity was quite successful. Success can be seen from the motivation, curiosity, and increased interaction of students marked by the number of students participating and being able to re-explain the results of projects made in groups in project-based learning.